Job satisfaction among Community-Based Rehabilitation (CBR) workers in caring for disabled persons in the east coast region of peninsular Malaysia - Hasan, Haliza; Aljunid, Syed Mohamed (Springer Nature, 2019)
Background: Job satisfaction influences staff retention, motivation, and performance in providing services. A considerable amount of published studies has reported on the job satisfaction level of healthcare workers, but to date, very few studies focused on Community-Based Rehabilitation (CBR) workers. This study aimed to explore the job satisfaction level among Community-Based Rehabilitation (CBR) workers and associated factors related to their overall job satisfaction. Methods: A one-year survey was conducted in three states of the east coast region of Peninsular Malaysia involving 204 CBR workers selected through universal sampling method where all CBR staff who fulfilled the inclusion criteria were selected as participants. Self-completed questionnaires consisted of 20 association factors on six-point Likert scale responses were distributed. Total mean satisfaction level and mean associated factors were reported in this study. Results: The results showed that the majority of the participants were between 20 and 40 years old (72%), female (96%), Malay (99%) and had 1–5 years of working experience. The mean total satisfaction score was 79.8 ± SD = 7.85. The highest mean satisfaction level for the associated factor was 4.6 ± SD = 0.59 with about 95% of the participants were satisfied that “CBR programme is a challenging work”, while the lowest satisfaction level for associated factor was on “salary of community-based rehabilitation staff is acceptable”, with mean score of 2.3 ± SD = 0.97 with about 59% of the participants felt dissatisfied. The results of this study determined that the highest dissatisfied factors among CBR workers were on salary. Conclusion: These findings provided useful information for policymakers to evaluate this issue for a sustainable CBR programme in the future. Trial registration: This study has been registered for trial as ‘retrospective registered’ in the Australian New Zealand Clinical Trials Registry (ANZCTR) (registration no.: ACTRN 12618001101279) on 5th October 2018